THE IMPLEMENTATION OF PICTURE SERIES IN IMPROVING STUDENTSâ€™ WRITING SKILLS OF SMPN2 BANGUNTAPAN - Yeni Fitri; Nanik Supriani (JELLT (Journal of English Language and Language Teaching), 2017)
The objectives of this study are to describe studentsâ€™ writing skills taught using picture series, to describe the studentsâ€™ writing skills taught using traditional method, to find out significant difference between studentsâ€™ writing skills taught using picture series and traditional method, and to find out a better class in producing writing skills e.g. experimental or control class. This research was experimental research. The population of this research was the eighth grade students of SMP N 2 Banguntapan. The samples were taken using lottery technique. For collecting the data, the researchers used paragraph writing test, in the pre-test and post-test. The data were analyzed using SPSS. The research findings showed that (1) the level of studentsâ€™ writing skills taught using picture series was â€œvery highâ€ at the category scale of 75-above, (2) the level of studentsâ€™ writing skills taught using traditional method was â€œhighâ€ at the category scale ofÂ  58.33-75, (3) the sig. (2-tailed) value of t-test was 0.000 implying there was a significant difference between studentsâ€™ writing skills taught using picture series and traditional method, and (4) the result of t-test showed that the experimental class produced better writing than the control class.